Safety, tolerability, pharmacokinetics, and pharmacodynamics of HBM9161, a novel FcRn inhibitor, in a phase I study for healthy Chinese volunteers - Desmond Y. H. Yap; Jojo Hai; Paul C. H. Lee; Xueying Zhou; Michael Lee; Yu Zhang; Meng Wang; Xiaoxiang Chen (Wiley, 2021)
Abstract Blockade of the binding between neonatal Fc receptor and IgG‐Fc reduces circulating IgG, and thus emerges as a potential therapy for IgG‐mediated autoimmune conditions. This was a double blind, randomized, single ascending dose study to evaluate the safety, pharmacokinetics, and pharmacodynamics of HBM9161 (a fully humanized Fc receptor monoclonal antibody) in healthy Chinese volunteers. Subjects were randomized to receive a single s.c. dose of HBM9161 or placebo in a 3:1 ratio in 3 dosing cohorts (340 mg, 510 mg, or 680 mg, respectively), and then followed up for 85 days. Study end points included incidence of adverse event (AE), serum drug concentration, IgG and its subclasses, and anti‐drug antibodies (ADAs). Twenty‐four subjects were randomized. Dose‐dependent reduction of total IgG occurred rapidly from baseline to reach nadir at day 11, then recovered steadily from day 11 to day 85. The mean maximum percentage reductions from baseline total IgG were 21.0 ± 9.3%, 39.8 ± 5.13%, and 41.2 ± 10.4% for subjects receiving HBM9161 340 mg, 510 mg, and 680 mg, respectively. The exposure of HBM9161 (areas under the curve [AUCs] and peak plasma concentration [Cmax]) increased in a more than dose‐proportional manner at the dose examined. All reported AEs were mild in severity. The most reported AEs in the HBM9161 groups were influenza‐like illness and rash. Two subjects developed ADA during the study period. A single s.c. dose of HBM9161 results in sustained and dose‐dependent IgG reduction, and was well‐tolerated at a dose up to 680 mg in Chinese subjects. The data warrant further investigation of its effects in IgG‐mediated autoimmune disorders.